Multiple-Stage Injection of Deep Hydrothermal Fluids in the Dolostone Reservoirs of Ordovician Majiagou Formation, Southern Ordos Basin - Yang, Zhaolin; Liu, Xinshe; Han, Xu; Zhou, Hu; Zhan, Sha; Gui, Xiaojun; Niu, Jihong; Wang, Ke (Frontiers in Earth Science, 2022)
The Middle Ordovician Majiagou Formation in the southern Ordos Basin develops a set of sub-and peri-tidal carbonate successions that were extensively dolomitized. Diagenetic dolomitization is widely investigated because dolostones provide high-quality gas reservoirs in the southern Ordos Basin. Nonetheless, the ultimate mechanism controlling dolomitization remains enigmatic. In this study, integrated geochemical indexes including carbon and oxygen isotopes, rare earth elements, and microthermometry, coupled with U-Pb dating and lithofacies and mineralogic studies, are investigated to elucidate the periods of hydrothermal fluids involved in the formation of different types of dolomites in the studied section from Ma5 member. The results reveal that the micritic dolomite matrix was formed under the involvement of low-salinity meteoric water in the mixing zone during a shallow-burial environment. The mixing zone of paleokarst possibly provided accommodation for this dolomitization. The fine-/medium-sized dolomites were formed due to interactions between hydrothermal fluids of comparatively low temperature and matrix carbonates, which occurred during the period of the Middle Jurassic. The dolomitic microbialites were formed due to the injection of high-temperature acid fluids associated with organic matter maturing. This dolomitization occurred during the period of the Late Jurassic according to U-Pb ages. The coarse-sized dolomite cements can be furtherly classified into two types according to different U-Pb ages and carbon-oxygen isotopes, although they are very similar with respect to mineralogic features. Comprehensive geochemical evidence revealed that the dolomitizing fluids of two types of dolomite cements were derived from hydrothermal fluids associated with periodical magmatism, which occurred during the period of the Early Cretaceous. This finding provides a new insight for elucidating the diagenetic process of reservoir dolostones from the Middle Ordovician in the Ordos Basin.